A fitorremediação como alternativa para recuperação do solo do lixão de Assú/RN - Paz, Fernanda Mayara Fernandes da (Universidade Federal Rural do Semi-Árido, 2020)
The problems arising from the improper disposal of solid waste, the contamination of soils by heavy metals, the high costs in the face of a possible recovery, can cause several problems for the current generation, as well as the future society. This is a topic of debate, exploring possible alternatives to solve them, economically and recovering, in fact, soils degraded by contaminating agents. Therefore, this article has as a general objective the possibility of recovery through phytoremediation. In the methodology, a qualitative research was carried out allowing the interpretation of an observed fact, of a descriptive character that will make it possible to describe characteristics of the variables, through a bibliographic review and documentary study. Phytoremediation for soil treatment in a landfill is viable using native plants from the caatinga, however, the use of Algaroba (Prosopis juliflora) plant native to the Peruvian biome, is well suited to the climate and soil of the Northeast and consequently the caatinga. There is also Cattail (Typha domingensis), King's Cigar (Nicotiana glauca Graham), Imburana (Commiphora Leptophlocos) and even conduct tests with plants from other ecosystems in order to mitigate the action of heavy metals. It was verified that it is possible to recover a landfill through phytoremediation, based on the characteristics of the landfill in Assú, using the species mentioned above, and it is up to the municipal public agency and society to be aware of the importance of a degraded soil treatment for a future generation. This will have long-term positive impacts for the region and eliminate the imminence of health risks for all. It is necessary to adopt urgent measures so that it does not result in greater damage.
Artigo
Keywords: Fitorremediação; Tratamento; Plantas; Solo; Phytoremediation; Treatment; Plants; Ground; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA